The Agturay of the Ili the elite of Ilocos, 1574-1661 - Apilado, Digna B. (Journal of History, 2010)
The 16th–17th centuries in Philippine history are significant in their being a period of change under Spanish colonial rule. Building on the previous researches of earlier scholars, this paper will reexamine the process of transition whereby Philippine communities were brought under Spanish rule, and how this process had changed Filipino culture and society. My focus is on the Ilocos region of northwestern Luzon as a geographic and cultural unit. The region will first be examined as part of the Southeast Asian world, and it will be shown that this connection to the larger world had led to the development within the region of extensive and established communities called ili or pagilian by the time the first Spanish explorations commenced in 1572. Certain features of Iloco society will benoted as the manifestation of cannawidan, the cultural matrix that is central to Ilocano ethnic identity. The Spanish accounts of the Juan de Salcedo expedition will be interpreted in terms of the Ilocano historical development before 1572, which could explain why the Ilocos region appeared to have been quickly “pacified” by the few Spanish who went there. The third part of the paper will look at historical events that indicate the stresses and fractures of an Asian society in transition under Spanish colonial rule. The encomienda system and the establishment of pueblo parishes found congruence in the prevailing social and political practices of the Ilocanos. But the Great Rebellion of 1660–61 in Ilocos, rarely mentioned in history textbooks, brought to the fore the conditions and character of the Ilocano elite and common people under Spanish rule. An analysis of the social and political consequences of the revolt’s aftermath would show a transformed Ilocano society by the close of the 17th century.